AN INVESTIGATION ON ADOLESCENTS' SOCIAL APPEARANCE LEVELS (Sample of Kırıkkale Province) - Yusuf Soylu; Fatih Atik; Mehmet Öçalan (ümit doğan üstün, 2017)
This research was carried out on 335 students (170 males and 165 females) in Anatolian High School, Science High School and Sports High School in Kırıkkale. The aim of the study was to compare the social appearance anxiety levels according to gender, age, school and sporting / non-sporting variables of adolescents who did and did not perform sports. The research method was the Social Appearance Anxiety Scale (SSI) scale. Hart et al. (2008) developed a self-report style measure designed to measure the emotional, cognitive, and behavioral anxieties experienced by an individual about appearance. The Turkish adaptation study of the scale was carried out by Doğan (2010). The Social Appearance Anxiety Scale is a measure of 16 items. High scores from the social anxiety scale, which measures social anxiety in one dimension, indicate that the anxiety of appearance is high. The Cronbach Alpha coefficient of your scale was .86 In the study, it was determined that the social appearance anxiety levels of adolescents did not show any significant difference according to age variable. It is seen that there is a significant difference according to the variables of the adolescents, gender, school and sporting/not doing.